Digital Winter. Connected vehicles for safer roads - Höglund, Jonas; Engstedt, Lena (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
Increased connectivity in cars, means that important information about infrastructure can be instantly transferred from the cars into a cloud. Car manufacturers have provided these systems for decades, but have just recently offered these connected functions to a broader customer base. Sharing data with the road authorities, however, is rare. Trafikverkets FOI-project Road Status Information wanted to explore the possibilities to gather road friction data from cars in daily traffic to monitor and improve the winter maintenance of the roads. A new cloud based digital solution from ÅF, in a joint venture with Volvo Cars, will now provide the Swedish Transport Administration of slippery road conditions data. One of the first initiatives in Europe to share data from vehicles in daily traffic with road authorities on a larger scale.